The Students Perception on The Use of English Movies in Learning Pronunciation - Masari, Andari Putri; Dewangga, Defian Aditya; Arochman, Taufik (UPA Bahasa Universitas Tidar And HISKI Kedu, 2025)
The student view about learning English pronunciation on the use of movies fourth and sixth students on various campuses. This study was aiming to finding the perception about the student’s perspectives in the use of movie in learning English especially in pronunciation and found that watching movies can have a positive impact on students' English vocabulary pronunciation. The type of this research used qualitative research. The researchers used a questionnaire in the form of google form, to collect data from 28 students, which is distributed through online messages. The instrument provided